Glycated and Oxidized Protein Degradation Products Are Indicators of Fasting and Postprandial Hyperglycemia in Diabetes - Ahmed, Naila; Babaei-Jadidi, Roya; Howell, Scott K; Thornalley, Paul J; Beisswenger, Paul J (Diabetes care, 2005)
OBJECTIVE:--To assess the relative importance of fasting and postprandial hyperglycemia to vascular dysfunction in diabetes, we have measured indicators of glycation, oxidative and nitrosative stress in subjects with type 1 diabetes, and different postprandial glucose patterns. RESEARCH DESIGN AND METHODS--Plasma and urinary levels of specific arginine- and lysine-derived advanced glycation end products, as well as oxidative and nitrosative products, were measured by liquid chromatography with triple quadrupole mass spectrometric detection (LC-MS/MS) after 2 months of treatment with insulin lispro or human regular insulin in 21 subjects participating in a cross-over study. Hb-bound early glycation (Amadori) products were also measured after each treatment period by high-performance liquid chromatography (fructosyl-valine Hb or HbA[subscript 1c] [A1C]:Diamat) and fructosyl-lysine Hb by LC-MS/MS (A1C:fructosyl-lysine). RESULTS:--In diabetic patients, the concentrations of protein glycation and oxidation-free adducts increased up to 10-fold, while urinary excretion increased up to 15-fold. Decreasing postprandial hyperglycemia with lispro gave 10-20% decreases of the major free glycation adducts, hydroimidazolones derived from methylglyoxal and 3-deoxyglucosone, and glyoxal-derived N[var epsilon]-carboxymethyl-lysine. No differences were observed in A1C:Diamat or A1C:fructosyl-lysine with lispro or regular insulin therapy in spite of significant decreases in postprandial glycemia with lispro. CONCLUSIONS:--We conclude that the profound increases in proteolytic products of proteins modified by advanced glycation endproducts in diabetic patients are responsive to changes in mean hyperglycemia and also show responses to changes in postprandial hyperglycemia.